(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the distribution, ecological status and population dynamics of the white stork (Ciconia ciconia) in the Ferghana Valley and in other regions of Uzbekistan. The natural habitat, food sources, and migration routes of white storks were studied. The study analyzed anthropogenic and natural factors contributing to the decline of the species, such as habitat reduction, power transmission networks, exposure to pesticides, depletion of water resources, reduction of food supply and climate change. The article has developed scientifically based proposals for the conservation and restoration of the white stork population. The results show that the white stork is a bioindicator bird that occupies an important place in the biodiversity of Uzbekistan, the number of which is closely related to environmental sustainability